Pengaruh alang-alang (Imperata cylindrica(L. Beauv.) terhadap tanaman karet pada tanah latosol dan podsolik merah- kuning=The Effect of Alang-Alang (Imperata Cylindrica (L.) Beauv.) on the Growth of Hevea Seedlings on La - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The purpose of this experiment was to study the competition and allelopathic effect of various population of along-alang (imperata cylindrica) on hevea seedlings grown on latosol and red yellow podzolic soils. Competition was studied by planting hevea and along-along of various population in a pot. Allelopathy was studied as competition experiment but the pots were supplied with complete nutrient to omit nutritional competition. The result showed that the growth of hevea seedlings was disturbed by alang alang due to competition and allelopathy. Due to competition dry weight of heve a seedlings decreased 14.86 percent in red yellow podzolic soil and 10.53 percent in latosol soil. Due to allelopathy dry weight of hevea seedlings decreased 18.73 percent in lalosol and 17.80 percent in red yellow podzolic soil. The effect of competition and allelopathy increased when the population of along-along increased.